2020
DOI: 10.3390/s20226555
|View full text |Cite
|
Sign up to set email alerts
|

Maturity Prediction in Yellow Peach (Prunus persica L.) Cultivars Using a Fluorescence Spectrometer

Abstract: Technology for rapid, non-invasive and accurate determination of fruit maturity is increasingly sought after in horticultural industries. This study investigated the ability to predict fruit maturity of yellow peach cultivars using a prototype non-destructive fluorescence spectrometer. Collected spectra were analysed to predict flesh firmness (FF), soluble solids concentration (SSC), index of absorbance difference (IAD), skin and flesh colour attributes (i.e., a* and H°) and maturity classes (immature, harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
5
11
0
Order By: Relevance
“…An approach based on UV excitation and cryo-imaging of autofluorescence in apple and grape tissue slices has allowed the topological localization of chlorophyll and flavonols in cuticle and cell walls, as a helpful technique to assess fruit quality and resistance to biotic and abiotic stress [93]. A fluorescence nondestructive spectral analysis of some cultivars of yellow peaches has also shown that fruit ripening is accompanied by a decrease in the signals typical of chlorophyll, the 683, 820 nm bands, and of flavonols and carotenoids, the 450-600 nm spectral region, in parallel with an increase in the band in the 600-650 nm range, consistently with the fluorescence spectral position of anthocyanins reported in the literature for grapes or onions [83,94,95]. Similarly, the content of anthocyanins estimated indirectly from the ratios of chlorophyll fluorescence measured in situ under different excitation wavelengths, by means of a portable fluorometric sensor device, has been proposed to optimize the harvest time for the table grape, Crimson seedless cultivar [96].…”
Section: Phenols and Polyphenolssupporting
confidence: 77%
“…An approach based on UV excitation and cryo-imaging of autofluorescence in apple and grape tissue slices has allowed the topological localization of chlorophyll and flavonols in cuticle and cell walls, as a helpful technique to assess fruit quality and resistance to biotic and abiotic stress [93]. A fluorescence nondestructive spectral analysis of some cultivars of yellow peaches has also shown that fruit ripening is accompanied by a decrease in the signals typical of chlorophyll, the 683, 820 nm bands, and of flavonols and carotenoids, the 450-600 nm spectral region, in parallel with an increase in the band in the 600-650 nm range, consistently with the fluorescence spectral position of anthocyanins reported in the literature for grapes or onions [83,94,95]. Similarly, the content of anthocyanins estimated indirectly from the ratios of chlorophyll fluorescence measured in situ under different excitation wavelengths, by means of a portable fluorometric sensor device, has been proposed to optimize the harvest time for the table grape, Crimson seedless cultivar [96].…”
Section: Phenols and Polyphenolssupporting
confidence: 77%
“…Both a* and h • are likely to be good indicators of maturity, with the latter being, in theory, the ideal parameter in fruit that possess a yellow intermediate step in the shift between green (immature) to orange-red (mature) or in fruit that simply go from green to yellow during ripening. Flesh a* and h • were strongly correlated with maturity in yellow peach cultivars [15]. In peaches and nectarines, fruit skin colour is influenced by environmental factors such as light [16][17][18] and irrigation [3,19].…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient work of the photosynthetic apparatus is associated with the addition of sucrose to the culture media and CO 2 deficiency [73,74]. Photoinhibition in peach plants and changes in the general functional state under the pressure of abiotic stress factors have been shown [75][76][77]. In our work, low photosynthetic activity and relatively low values of photosynthesis Y (II) efficiency were associated with a low chlorophyll amount in vitro.…”
Section: Discussionmentioning
confidence: 51%